SOME CONSIDERATIONS ON FOREIGN LANGUAGE TEACHING IN THE FACULTY OF ARTS, INCLUDING USES OF THE LANGUAGE LABORATORY AND THE QUESTION OF A PERIOD OF RESIDENCE ABROAD. - rewer, E. F. B. (مجلة كلية الاداب, 1972)
The fact that the Faculty of Arts and Education in Benghazi has now become, for better or worse, the Faculty of Arts, does not mean to say that interest in methods of teaching has entirely dis appeared here. On the contrary, there is probably an increase in interest for several reasons, including : (a) this year's change of syllabus in all departments; (b) the need for the constant re appraisal of the aims and objects of courses; (c) the general feel ing of unrest in so many of the world's universities; (d) the influx of new lecturers, some fresh from training, others bringing in the benefit of their experience from other universities; (e) the near certainty that many of our graduates will continue to join the teaching profession; (f) our interest in the standards of our fresh men; (g) the possibility of some use being made of Libyan Radio and Television for educational purposes, (especially language teaching); — and still the list is by no means exhausted. But of course, what is of most immediate concern to the staff of the Faculty of Arts at the present time is not so much what the effect of our graduates is going to be as teachers in the schools, but 35 rather what effect our own teaching is having on our students both as scholars and as individual personalities. Some very fundamental questions are being asked in the world at large about the aims and objects of language teaching, and it will be well for us in the University of Libya, foreign tea chers as well as Libyans, students as well as staff, to ask ourselves some of these basic questions. Firstly, for example, « Why are languages taught in the universities ? Which languages need to be taught in Libya ? To what level ? » Secondly, « Are these languages being taught efficiently Thirdly, « What do recent (i.e. post World War II) innovations have to offer which can be of help ? » And lastly, « Do we need to change our objectives and methods ? » Though I may have formed my own opinions on some or all of these points, I have no intention of laying down the law on them : they are open to debate, and answers which may be found to them now may have to be changed again in the course of a few years. It might well, however, be a useful thing for the Uni versity of Libya to institute an annual or biennial conference be tween the Foreign Languages Department of the Faculty of Arts and that of the Faculty of Education — preferably annually I think, but to be held alternately in Benghazi and Tripoli, perhaps in the September of each year. Some open debates might be ar ranged to which might be invited interested representatives from other Faculties, from the Ministry of Education, from Teachers' Training Colleges, and from among our own graduates and the general public. Whether such a conference is held or no, some thought might well be given to the question of how closely, if at all, the programmes of the two departments should be related. Should they be basically the same ? If so, Arts students should presumably be given an additional advanced course in literature 36